Associations of Placental Oxidative Stress with Exposure to Gestational Air Pollution: Evidence from the UPSIDE Cohort - Emily A. Craig; Yan Lin; Yihui Ge; Xiangtian Wang; Otgondelger Enkhtaivan; Don K. Harrington; Richard K. Miller; Susan K. Murphy; Sally W. Thurston; Philip K. Hopke; Emily S. Barrett; Thomas G. O'Connor; et al. (Environmental Research, 2026)

Combined exposure to hypoxia and 17α-ethinylestradiol alters reproductive traits in marine medaka - Xian Qin; Jiezhang Mo; Huiju Lin; Yi Yang; Emily Sze Wan Wong; Min Pan; Sidney Man Ngai Chan; Rudolf Shiu Sun Wu; William Ka Fai Tse; Keng Po Lai (Aquatic Toxicology, 2026)

Identify conservation gaps and devise sustainable use strategies using orchid flora as a proxy - Hong Liu; Emily Jefferson; Shao-Ting Lin; Che-Yu Lin; Chun-Ming Chen; Dominic Mellone; Wen-Chieh Tsai (Biodiversity and Conservation, 2026)

Pathological findings in 61 free-ranging leopards (Panthera pardus) from the Greater Kruger National Park, South Africa. Part Two: non-parasitic conditions - Emily P. Mitchell; Lin-Mari de Klerk-Lorist; Peter Buss; Bjorn Reininghaus; Roy Bengis (Journal of Comparative Pathology, 2026)

Connecting with nature: The missing link between a satisfied life and a healthy life? - Kate Sollis; Usitha Rajeevan; Lily M van Eeden; Kate Lee; Lucy Keniger; Brenda B Lin; Pauline Marsh; Emily J Flies (Ambio, 2026)
Nature connection is an important leverage point for human wellbeing and planetary health. In this paper, we examine the varying relationships between nature connection and wellbeing measures through a nationally-representative survey in Australia. We find a positive association between nature connection and two measures of wellbeing: life satisfaction (measured through the personal wellbeing index; PWI) and health-related quality-of-life (measured through the Australian Quality of Life (AQoL) tool). Nature connection was associated with all PWI life domains with a strength of association similar to the relationship between income and PWI. We find a stronger association between nature connection and how satisfied a person feels about their life (PWI) than how well a person feels they function in life (AQoL). Those with higher levels of nature connection tend to have greater life satisfaction than expected from their health-related quality-of-life. These findings highlight the potential to improve wellbeing via nature connection, by expanding opportunities to meaningfully connect with nature.

Resource‐Dependent Metabolic and Biogeochemical Consequences of Viruses in Agricultural Soils - Guixiang Zhou; Junxi Liu; Fangming Liu; Yu Xiao; Emily B. Graham; Yakov Kuzyakov; Mao Ye; Xiuli Xin; Lin Chen; Congzhi Zhang; Donghao Ma; Zongzhi Wu; et al. (Global Change Biology, 2026)
Soil viruses are crucial for microbial life, biogeochemical cycles of carbon and nutrients, and for microbial necromass formation. We hypothesized that the effects of viruses on these processes depend on organic matter and nutrient availability in soils. Here, we combined a 34‐year long‐term fertilization trial, 150 sequenced soil metagenomes, and microcosm experiments to explore how viruses modulate carbon and nutrient dynamics depending on resource availability. We uncovered 2789 viral populations (vOTUs) grouping into 301 viral clusters, 91% of which were previously unknown. Organically fertilized soils harbored most lytic viruses carrying diverse element cycling‐related auxiliary viral genes (AVGs) acquired through co‐evolution and horizontal gene transfer. Synthesis and heterologous expression assays further indicated that four AVGs (i.e., cbhA , pel , wbpD , GT2 ) had higher transcript levels in Escherichia coli under nutrient rich than nutrient poor conditions. Addition of virus particles to soils raised microbial carbon use efficiency (CUE; biomass production relative to carbon uptake) and accelerated microbial turnover leading to boosted microbial necromass formation by 14%. Conversely, in soils without organic fertilizers, viruses facilitate bacterial adaptation to stress (e.g., defense system and interference competition) and accelerate microbial decomposition of organic matter. 35 days after virus addition, CO 2 and N 2 O emissions increased by 41% and 52%, respectively. Finally, we propose the Viral Entombing‐Priming (VEP) framework to describe the contrasting roles of viruses in carbon and nutrient dynamics depending on soil fertility. This work reveals the viral “Matthew effect” ( the rich get richer and the poor get poorer ) in resource‐rich and resource‐poor soils and could unlock nature‐based pathways to raise carbon and nutrient retention for sustainable agriculture.

A two-step Bayesian clustering approach to relate PFAS mixture profiles and dietary patterns in early pregnancy - Xuzhi Wang; Tamarra James-Todd; Ami R. Zota; Luke Shawler; Pi-I.D. Lin; Emily Oken; Jorge Chavarro; Sharon Sagiv; Briana J.K. Stephenson (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Pathological findings in 61 free-ranging leopards (Panthera pardus) from the Greater Kruger National Park, South Africa. Part One: parasites - Emily P. Mitchell; Lin-Mari de Klerk-Lorist; Peter Buss; Bjorn Reininghaus; Roy Bengis (Journal of Comparative Pathology, 2026)

Prenatal urinary biomarkers of metal and metalloid exposure and child neurodevelopmental outcomes in Puerto Rico - Savannah M. Sturla Irizarry; Amber L. Cathey; Emily Zimmerman; Wei Hao; Yi-Ting Lin; Bhramar Mukherjee; Zaira Y. Rosario Pabón; Gredia Huerta Montañez; Carmen M. Vélez Vega; Akram N. Alshawabkeh; José F. Cordero; John D. Meeker; et al. (Environmental Research, 2026)

Development of a Stereolithography 3D Printing-Based Micropatterning Method to Study Endothelial-to-Mesenchymal Transition Mechanobiology - Karina Bender; Sarah Chesley; Jay Lesny Drake; Megan Ho; Emily Lin; Kathryn Saxton; Ninava Sharma; Christina K. Tripsas; Qian Li; Jeffrey J. Hsu (Annals of Biomedical Engineering, 2026)
Endothelial-to-mesenchymal transition (EndMT) is the process of endothelial cells undergoing molecular changes that shift their phenotype from that of endothelial cells to that of mesenchymal-like cells. It is a crucial developmental process that has been implicated in various physiological and pathological conditions. EndMT has gained attention as a potential therapeutic target for cardiovascular disease processes, including atherosclerosis, myocardial fibrosis, and vascular calcification. In addition to the assessment of endothelial and mesenchymal markers, the behavioral mechanics of endothelial cells, such as migration and invasion, are often used to identify endothelial cells that have undergone EndMT. However, whether cell chirality may be another mechanobiological marker of EndMT remains unclear. In this study, we aimed to develop an accessible micropatterning platform and created a stereolithography (SLA) 3D printing-based polydimethylsiloxane (PDMS) protein-stamp fabrication platform to create customized patterns of ECM proteins to study endothelial cell chirality during EndMT. Human aortic endothelial cells (HAECs) were treated with the inflammatory cytokine tumor necrosis factor-α (TNF-α), which resulted in the downregulation of the endothelial marker ENOS3 and the upregulation of the mesenchymal markers N-cadherin and transgelin, supporting the induction of EndMT. HAECs were seeded onto fibronectin stripe micropatterns, and cell chirality was measured using custom cell-profiling software. HAECs treated with TNF-α exhibited a shift in cell orientation by approximately 18°, supporting altered cell chirality during TNF-α-induced EndMT. Our work innovates novel methods of studying EndMT by developing a flexible and cost-effective protein-stamp fabrication and image analysis pipeline. This pipeline can be used by researchers to study the endothelial cell chirality in response to EndMT induction.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Multi-species aggregation and movement patterns of danaid butterflies (Nymphalidae: Danainae) in Hong Kong - Yuet Fung Ling; Emily E. Jones; Nicole Yu; Kirsten Boehm; Long In Cheung; Chun Hoi Law; Even Y. M. Leung; Megan Mei Yan Low; Rui Wang; Wing Kwong Yau; Sui Fai Hydrogen Pun; Yuk Lin Colleen Chiu; et al. (Journal of Insect Conservation, 2026)
Danaid butterflies (Nymphalidae: Danainae) in Asia form seasonal aggregations and/or exhibit migratory flights similar to those of the North American monarch ( Danaus plexippus ). In contrast to this well-studied single-species system, however, Asian danaids form smaller multi-species aggregations and show seasonal movements which remain relatively understudied. In this study, we used publicly reportable stickers to tag 15,918 danaid butterflies from 13 species and five genera ( Euploea , Tirumala , Danaus , Ideopsis , Parantica ) over four years in Hong Kong to elucidate patterns of seasonal aggregation and movements. Species assemblages were distinct at forested valley habitats versus open sites rich in pyrrolizidine alkaloid (PA) plants. Using mark-recapture, we estimated up to 16,000 butterflies in a single aggregation. Recoveries of 1,503 tags (50.6% reported by the public) revealed local movements of 78 individuals, but no butterflies were reported outside Hong Kong. The observed variation in aggregation dynamics and movement patterns indicate interspecific differences in site selection, overwintering strategies, and orientation of seasonal movement. Regional collaboration across southern China and the Indochinese region is necessary to understand these complicated patterns and inform the conservation of sensitive overwintering and migratory phenomena. Implications for insect conservation Aggregation and migration of Asian danaid butterflies may be similarly vulnerable to habitat and climate changes that have led to extensive declines in the migratory monarchs in North America. Our study highlights the need for dynamic and comprehensive conservation strategies that adequately consider the requirements of many species involved in the multi-species danaid systems in tropical and subtropical Asia.

Nature connection, wellbeing and pro-environmental behaviour across an urban gradient: Understanding the regional sweet spot - Brenda B. Lin; Kate Sollis; Emily J. Flies; Pauline Marsh (Ambio, 2026)
While there is growing understanding of the impact of urbanisation on nature access and nature connection, little is known about this pattern across the rural-urban gradient. Through a nationally-representative survey, we explore relationships of nature connection, wellbeing, and pro-environment behaviour across remote, regional, and urban Australia. We also examine two open-ended questions about an individual’s everyday interaction and meaningful experiences with nature. The results show non-linear relationships with stronger levels of nature connection in remote and outer regional areas of Australia, while personal well-being and pro-environmental behaviour scores were higher in outer regional Australia. Open-ended questions revealed that increasing urbanisation led to more limited interactions or meaningful experiences with nature, and individuals in remote and outer regional areas feel immersed in nature, while individuals in major cities travel to visit nature. Regional areas appear to provide opportunities for immersive nature while also access to key services that contribute to wellbeing.

Protecting nature in diverse ways: The socio-demographic spread of benefits from connecting with nature - Kate Sollis; Lily van Eeden; Usitha Rajeevan; Kate Lee; Brenda Lin; Lucy Keniger; Pauline Marsh; Emily Flies (Ambio, 2026)
Nature connection and its relationships with stewardship vary across social and environmental contexts. Through a nationally representative survey in Australia, this study examined engagement in four different pro-environmental behaviours (PEBs) (advocacy, consumer-conscious, conservation, and gardening), their socio-demographic correlates, and the associations with both nature connection and well-being. We found strong associations between nature connection and all examined PEBs; however, different groups were more likely to engage in different types of PEBs. For example, younger adults are more likely to engage in advocacy and conservation behaviours, while older Australians are more likely to engage in consumer-conscious behaviours and gardening. All PEBs were significantly associated with well-being; however, only the advocacy behaviours variable remained significant when including nature connection as a control variable. These findings highlight the importance of biodiversity policies that holistically enhance nature connection for a range of people, alongside sustainability measures to support the well-being of both people and planet.

Prenatal air pollution exposure and placental vasculature development among participants of the UPSIDE cohort study - Shivram Kumar; Carolyn M. Salafia; Ruchit Shah; Theresa Girardi; Richard K. Miller; Sally W. Thurston; Philip K. Hopke; David Skrill; Jessica Brunner; Donald Harrington; Yihui Ge; Yan Lin; et al. (Environmental Research, 2025)

PM2.5 and NO2 exposure during pregnancy and measures of fetal size and attained size at birth - Nafisa Nawal Islam; Sally W. Thurston; Donald Harrington; Yihui Ge; Samuel Weisenthal; Jessica Brunner; Richard K. Miller; Philip K. Hopke; Yan Lin; Emily S. Barrett; Thomas G. O’Connor; Junfeng Zhang; et al. (Air Quality, Atmosphere & Health, 2025)

A Genomic Exploration of the Possible De‐Extirpation of the Zanzibar Leopard - Xin Sun; Emily Louisa Cavill; Ashot Margaryan; Jianqing Lin; Søren Thingaard; Tamrini A. Said; Shyam Gopalakrishnan; M. Thomas P. Gilbert (Molecular Ecology, 2025)
The recently extirpated Zanzibar leopard was the only known African leopard ( Panthera pardus spp.) population restricted exclusively to a major island habitat. Although its demise was driven through habitat change and conflict with humans, given its role as a keystone species for the Zanzibar Archipelago, its successful potential reintroduction might offer a means for helping preserve the natural biodiversity of its former habitat. Whether this is feasible, however, would be contingent on both whether closely related source populations can be identified on mainland Africa, and whether the Zanzibar form exhibited any special adaptations that might need to be considered when choosing such a source. In light of these questions, we genomically profiled two of the six known historic specimens, to explore whether they represent a realistic candidate for de‐extirpation through reintroduction. Our analyses indicate that despite its geographical separation, the Zanzibar leopard shared a close genetic relationship with mainland East African individuals. Furthermore, although its uniqueness as an island population was emphasised by genomic signatures of high inbreeding and increased mutation load, the latter similar to the level of the critically endangered Amur leopard ( P. p. orientalis ), we find no evidence of functionally significant genetic diversity unique to Zanzibar. We therefore conclude that should attempts to restore leopards to Zanzibar be considered, then mainland East African leopards would provide a suitable gene pool.

Walruses are potentially exposed to paralytic shellfish toxin concentrations that impact their health during Alexandrium blooms in the Alaskan Arctic - Patrick Charapata; Evangeline Fachon; Donald M. Anderson; Gay Sheffield; Emily K. Bowers; Robert S. Pickart; Peigen Lin; Kathi A. Lefebvre (Harmful Algae, 2025)

Contrasting short-term dynamics of supraglacial ponds along the Hindu Kush-Himalaya revealed by PlanetScope imagery and deep learning - Xingyu Xu; Lin Liu; Lingcao Huang; Yan Hu; Guoqing Zhang; Adina Racoviteanu; Emily Victoria Liu; YingTo Agnes Chan (Global and Planetary Change, 2025)

Saxitoxin Linked to Deaths of Northern Fur Seals in the Southeast Bering Sea - Kathi A. Lefebvre; Chelsea M. Campbell; Lauren M. Divine; Paul Melovidov; Hanna Hellen; Kathy Burek Huntington; Emily K. Bowers; Natalie Rouse; Evangeline Fachon; Thomas J. Farrugia; Robert S. Pickart; Peigen Lin; et al. (Marine Mammal Science, 2025)
In August 2024, a northern fur seal mortality event was observed on St. Paul Island, AK in the southeast (SE) Bering Sea. Ten seals in good body condition were found dead along with large accumulations of dead fish on Benson Beach located on St. Paul Island. Full necropsies of the five available adult seals, one pup, and several fish did not reveal any overt causes of death. Testing of tissues for the algal neurotoxins domoic acid (DA) and saxitoxin (STX) confirmed the presence of STX in multiple tissues and physiological exposure in all five adult NFS and the two fish available for testing. DA was not detected in any samples. Complimentary samples of the SE Bering Sea ecosystem during the same time frame and location as the die off revealed bloom densities of Alexandrium catenella (the dinoflagellate that produces STX), large A. catenella cyst beds, and high prevalences of STX in fish (100%, n = 22), zooplankton (93%, n = 28), clams (100%, n = 10) and worms (93% n = 15) in the foraging area of NFS. High STX concentrations were observed in fish, clams, worms, and NFS urine, providing compelling evidence for a STX poisoning event.

Characterization of astaxanthin isomers in different types of salmon filets and human plasma after salmon consumption - Peiran Lu; Nichole Reisdorph; Audrey E. Hendricks; Richard Reisdorph; Kevin Quinn; Michael Armstrong; Cole Michel; Katrina A. Doenges; Daniel N. Frank; Wayne W. Campbell; Emily B. Hill; Nancy F. Krebs; et al. (Food Chemistry, 2025)

Early life phthalate exposure impacts gray matter and white matter volume in infants and young children - Emily J. Werder; Kun Lu; Chih-Wei Liu; Jake E. Thistle; Julia E. Rager; Gang Li; Zhengwang Wu; Tengfei Li; Li Wang; Dale P. Sandler; John H. Gilmore; Joseph Piven; et al. (Environmental Research, 2025)

Phytoplankton Exhibit Diverse Responses to Different Phases of Upwelling in the California Current System - Yuan Yu Lin; Olivia Torano; Emily Pierce; Claire Till; Matthew Hurst; Astrid Schnetzer; Harvey Seim; Adrian Marchetti (Environmental Microbiology, 2025)
Eastern boundary upwelling currents are some of the most biologically productive and diverse regions in the world's oceans. Driven by equatorward winds and Ekman transport, surface waters are transported offshore and replaced by cold, nutrient‐rich deep waters that seed extensive phytoplankton blooms. Studying phytoplankton community succession and physiological acclimation during the initial stages of upwelling is critical to building a comprehensive understanding of phytoplankton responses to upwelling in these important regions. Additionally, factors like lateral transport, seed population dynamics and physiological and molecular shifts are conducive to shaping the community assemblage and primary productivity. This study examines how phytoplankton gene expression and resulting physiology change between early and later phases of upwelling. By incorporating metatranscriptomic analyses and stable isotope incubations to measure nutrient uptake kinetics into our assessment of early and later upwelling stages, we observed variability in phytoplankton assemblages and differential gene expression of phytoplankton that were de‐coupled from their physiology. We show that the gene expression response to a fresh upwelling event precedes their physiological response. Ultimately, understanding how phytoplankton change through the course of an upwelling event is critical to assessing their importance to regional biological rate processes, trophic systems and resulting biogeochemistry.

Monitoring of genetically modified crops in food products in Singapore - Yanwen Wang; Kung Ju Lin; Emily Huey Shyan Teo; Yong Quan Tan; Yuansheng Wu; Kern Rei Chng; Joanne Sheot Harn Chan; Li Kiang Tan (Food Control, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Assessing greenspace and cardiovascular health through deep-learning analysis of street-view imagery in a cohort of US children - Li Yi; Sheryl Rifas-Shiman; Marcia Pescador Jimenez; Pi-I Debby Lin; Esra Suel; Perry Hystad; Andrew Larkin; Steve Hankey; Wenwen Zhang; Jochem Klompmaker; Emily Oken; Marie-France Hivert; et al. (Environmental Research, 2025)

Residue depletion profiles and withdrawal intervals of florfenicol and its metabolite florfenicol amine in plasma and milk of lactating goats after repeated subcutaneous administrations - Qiran Chen; Zhoumeng Lin; Jennifer L. Davis; Emily Toney; Maaike O. Clapham; Xue Wu; Lisa A. Tell (Regulatory Toxicology and Pharmacology, 2024)

Prenatal blood metals, per- and polyfluoroalkyl substances and antigen- or mitogen-stimulated cord blood lymphocyte proliferation and cytokine secretion - Anna R. Smith; Pi-I.D. Lin; Sheryl L. Rifas-Shiman; Abby F. Fleisch; Robert O. Wright; Brent Coull; Patricia W. Finn; Emily Oken; Diane R. Gold; Andres Cardenas (Environmental Research, 2024)

Residential Proximity to Metal-Emitting Industries and Toenail Metal Concentration in the US Gulf States - Joyce J. Y. Lin; Emily J. Werder; Kaitlyn G. Lawrence; W. Braxton Jackson; Dale P. Sandler; Aisha S. Dickerson; Lawrence S. Engel; Ana M. Rule (Exposure and Health, 2024)

Systemic oxidative stress levels during the course of pregnancy: Associations with exposure to air pollutants - Xiangtian Wang; Yan Lin; Yihui Ge; Emily Craig; Xiaodong Liu; Richard K. Miller; Sally W. Thurston; Jessica Brunner; Emily S. Barrett; Thomas G. O'Connor; David Q. Rich; Junfeng (Jim) Zhang (Environmental Pollution, 2024)

Blueprint for the design, construction, and validation of a plastic and phthalate-minimised laboratory - Cassandra Rauert; Xianyu Wang; Nathan Charlton; Chun-Yin Lin; Cheng Tang; Ian Zammit; Ayomi Jayarathne; Christos Symeonides; Emily White; Michael Christensen; Valentina Ponomariova; Jochen F. Mueller; et al. (Journal of Hazardous Materials, 2024)

Cross-sectional and prospective associations of early childhood circulating metals with early and mid-childhood cognition in the Project Viva cohort - Ruwan Thilakaratne; Pi-I D. Lin; Sheryl L. Rifas-Shiman; Julio Landero; Robert O. Wright; David Bellinger; Emily Oken; Andres Cardenas (Environmental Research, 2024)

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

RNF4 prevents genomic instability caused by chronic DNA under-replication - Marissa K. Oram; Ryan M. Baxley; Emily M. Simon; Kevin Lin; Ya-Chu Chang; Liangjun Wang; Chad L. Myers; Anja-Katrin Bielinsky (DNA Repair, 2024)

Progress and evolution of hotspots in butterfly diversity research in green spaces - Ying Lin; Shanjun Huang; Wenqiang Fang; Shiyuan Fan; Chengyu Ran; Emily Dang; Weicong Fu; Zhipeng Zhu (Environmental Science and Pollution Research, 2024)

Phenolic composition and antioxidant capacity of betel inflorescence extract in a simulated oral environment - Pangzhen Zhang; Ahmad Reza; Emily Ng; Kimtrang Nguyen; Sheng Lin; Zijian Liang; Yipeng Chen; Nicola Cirillo (Food Chemistry, 2024)

Cell size‐dependent species sensitivity to nanoparticles underlies changes in phytoplankton diversity and productivity - Yiping Zuo; Michael Southard; Qianna Xu; Guangxing Zhang; Emily Skibinski; Nicole Moon; Lan Gan; Yongsheng Chen; Lin Jiang (Global Change Biology, 2024)
Nanoparticle pollution has been shown to affect various organisms. However, the effects of nanoparticles on species interactions, and the role of species traits, such as body size, in modulating these effects, are not well‐understood. We addressed this issue using competing freshwater phytoplankton species exposed to copper oxide nanoparticles. Increasing nanoparticle concentration resulted in decreased phytoplankton species growth rates and community productivity (both abundance and biomass). Importantly, we consistently found that nanoparticles had greater negative effects on species with smaller cell sizes, such that nanoparticle pollution weakened the competitive dominance of smaller species and promoted species diversity. Moreover, nanoparticles reduced the growth rate differences and competitive ability differences of competing species, while having little effect on species niche differences. Consequently, nanoparticle pollution reduced the selection effect on phytoplankton community abundance, but increased the selection effect on community biomass. Our results suggest cell size as a key functional trait to consider when predicting phytoplankton community structure and ecosystem functioning in the face of increasing nanopollution.

Pharmacokinetics, tissue residue depletion, and withdrawal interval estimations of florfenicol in goats following repeated subcutaneous administrations - Xue Wu; Zhoumeng Lin; Emily Toney; Maaike O. Clapham; Scott E. Wetzlich; Jennifer L. Davis; Qiran Chen; Lisa A. Tell (Food and Chemical Toxicology, 2023)

Significant catalyst savings and reaction kinetics enhancement for catalytic micro-combustors via non-uniform catalyst segmentation - Emily Lin; Chad T. Wilson; Arny Leroy; Sili Deng (Chemical Engineering Journal, 2023)

Novel perfluoroalkyl substances (PFAS) discovered in whole blood using automated non-targeted analysis of dried blood spots - Jeremy P. Koelmel; Elizabeth Z. Lin; Emily Parry; Paul Stelben; Emma E. Rennie; Krystal J. Godri Pollitt (Science of The Total Environment, 2023)

Up in the air: Polyfluoroalkyl phosphate esters (PAPs) in airborne dust captured by air conditioning (AC) filters - Alina S. Timshina; William J. Sobczak; Emily K. Griffin; Ashley M. Lin; Timothy G. Townsend; John A. Bowden (Chemosphere, 2023)

Exploratory analysis of a cluster randomized controlled trial of a multi-strategy intervention delivered via online canteens on improving the nutritional quality of primary school students’ pre-ordered foods & drinks at recess - Tessa Delaney; Jacklyn Jackson; Christophe Lecathelinais; Sze Lin Yoong; Luke Wolfenden; Rachel Sutherland; Emily Webb; Rebecca Wyse (Appetite, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

Wearable Passive Samplers for Assessing Environmental Exposure to Organic Chemicals: Current Approaches and Future Directions - Joseph O. Okeme; Jeremy P. Koelmel; Emily Johnson; Elizabeth Z. Lin; Dong Gao; Krystal J. Godri Pollitt (Current Environmental Health Reports, 2023)

Early pregnancy essential and non-essential metal mixtures and maternal antepartum and postpartum depressive symptoms - Lisa B. Rokoff; Andres Cardenas; Pi-I D. Lin; Sheryl L. Rifas-Shiman; Robert O. Wright; Michelle Bosquet Enlow; Brent A. Coull; Emily Oken; Susan A. Korrick (NeuroToxicology, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

The characteristics of ambient air quality in urban forest areas and other urban areas of Fuzhou city, China - Weicong Fu; Yuxuan Qiao; Chenxi Que; Hongkui Chen; Emily Dang; Jianwen Dong; Shuangyi Lin (Environment, Development and Sustainability, 2022)

Structural basis for the functional properties of the P2X7 receptor for extracellular ATP - Lin-Hua Jiang; Emily A. Caseley; Steve P. Muench; Sébastien Roger (Purinergic Signalling, 2021)
The P2X7 receptor, originally known as the P2Z receptor due to its distinctive functional properties, has a structure characteristic of the ATP-gated ion channel P2X receptor family. The P2X7 receptor is an important mediator of ATP-induced purinergic signalling and is involved the pathogenesis of numerous conditions as well as in the regulation of diverse physiological functions. Functional characterisations, in conjunction with site-directed mutagenesis, molecular modelling, and, recently, structural determination, have provided significant insights into the structure–function relationships of the P2X7 receptor. This review discusses the current understanding of the structural basis for the functional properties of the P2X7 receptor.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

The clinical utility of proton magnetic resonance spectroscopy in traumatic brain injury: recommendations from the ENIGMA MRS working group - Brenda L Bartnik-Olson; Jeffry R Alger; Talin Babikian; Ashley D Harris; Barbara Holshouser; Ivan I Kirov; Andrew A Maudsley; Paul M Thompson; Emily L Dennis; David F Tate; Elisabeth A Wilde; Alexander Lin (Brain Imaging and Behavior, 2021)

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

The impact of meteorological conditions on Air Quality Index under different urbanization gradients: a case from Taipei - Zhipeng Zhu; Yuxuan Qiao; Qunyue Liu; Conghua Lin; Emily Dang; Weicong Fu; Guangyu Wang; Jianwen Dong (Environment, Development and Sustainability, 2021)

Balanced stochastic versus deterministic assembly processes benefit diverse yet uneven ecosystem functions in representative agroecosystems - Wenjing Liu; Emily B. Graham; Yang Dong; Linghao Zhong; Jianwei Zhang; Chongwen Qiu; Ruirui Chen; Xiangui Lin; Youzhi Feng (Environmental Microbiology, 2021)
Summary Ecological assembly processes, by influencing community composition, determine ecosystem functions of microbiomes. However, debate remains on how stochastic versus deterministic assembly processes influence ecosystem functions such as carbon and nutrient cycling. Towards a better understanding, we investigated three types of agroecosystems (the upland, paddy, and flooded) that represent a gradient of stochastic versus deterministic assembly processes. Carbon and nutrient cycling multifunctionality, characterized by nine enzymes associated with soil carbon, nitrogen, phosphorous and sulfur cycling, was evaluated and then associated with microbial assembly processes and co‐occurrence patterns of vital ecological groups. Our results suggest that strong deterministic processes favour microorganisms with convergent functions (as in the upland agroecosystem), while stochasticity‐dominated processes lead to divergent functions (as in the flooded agroecosystem). To benefit agroecosystems services, we speculate that it is critical for a system to maintain balance between its stochastic and deterministic assembly processes (as in the paddy agroecosystem). By doing so, the system can preserve a diverse array of functional traits and also allow for particular traits to flourish. To further confirm this speculation, it is necessary to develop a systematic knowledge beyond merely characterizing general patterns towards the associations among community assembly, composition, and ecosystem functions.

Contribution of Val/Ile87 residue in the extracellular domain in agonist-induced current responses of the human and rat P2X7 receptors - Emily A Caseley; Stephen P Muench; Lin-Hua Jiang (Purinergic Signalling, 2020)
The P2X7 receptor (P2X7R) is an ATP-gated cation channel with a critical role in many physiological and pathological processes, and shows prominent functional differences across mammalian species, exemplified by larger current responses of the rat (r) P2X7R to ATP and its analogue BzATP and a greater sensitivity to agonists compared with the human (h) P2X7R. Here, we showed that substitution of Val87 residue in the extracellular domain of the hP2X7R with isoleucine in the rP2X7R increased the current responses of the hP2X7R to both ATP and BzATP. Conversely, introduction of reciprocal I87V mutation in the rP2X7R led to a noticeable but statistically insignificant reduction in the current responses of the rP2X7R to ATP and BzATP. The mutations did not affect the sensitivity of the human and rat P2X7Rs to ATP and BzATP. These results suggest a contribution of Val/Ile87 in agonist-induced current responses of human and rat P2X7Rs, which helps to better understand the molecular determinants for species-dependent function of the mammalian P2X7Rs.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The asymmetric function of Dph1–Dph2 heterodimer in diphthamide biosynthesis - Min Dong; Emily E. Dando; Ilana Kotliar; Xiaoyang Su; Boris Dzikovski; Jack H. Freed; Hening Lin (JBIC Journal of Biological Inorganic Chemistry, 2019)

Gross primary productivity of a large metropolitan region in midsummer using high spatial resolution satellite imagery - David L. Miller; Dar A. Roberts; Keith C. Clarke; Yang Lin; Olaf Menzer; Emily B. Peters; Joseph P. McFadden (Urban Ecosystems, 2018)

Speciation in the mountains and dispersal by rivers: Molecular phylogeny of Eulamprus water skinks and the biogeography of Eastern Australia - Mitzy Pepper; Joanna Sumner; Ian G. Brennan; Kate Hodges; Alan R. Lemmon; Emily Moriarty Lemmon; Garry Peterson; Daniel L. Rabosky; Lin Schwarzkopf; Ian A. W. Scott; Glenn Shea; J. Scott Keogh (Journal of Biogeography, 2018)
Aim To develop a robust phylogeny for the iconic Australian water skinks ( Eulamprus ) and to explore the influence of landscape evolution of eastern Australia on phylogeographic patterns. Location Eastern and south‐eastern Australia. Methods We used Sanger methods to sequence a mitochondrial DNA (mt DNA ) locus for 386 individuals across the five Eulamprus species to elucidate phylogeographic structure. We also sequenced a second mt DNA locus and four nuclear DNA ( nDNA ) loci for a subset of individuals to help inform our sampling strategy for next‐generation sequencing. Finally, we generated an anchored hybrid enrichment ( AHE ) approach to sequence 378 loci for 25 individuals representing the major lineages identified in our Sanger dataset. These data were used to resolve the phylogenetic relationships among the species using coalescent‐based species tree inference in * BEAST and ASTRAL . Results The relationships between Eulamprus species were resolved with a high level of confidence using our AHE dataset. In addition, our extensive mt DNA sampling revealed substantial phylogeographic structure in all species, with the exception of the geographically highly restricted E . leuraensis . Ratios of patristic distances (mt DNA / nDNA ) indicate on average a 30‐fold greater distance as estimated using the mt DNA locus ND 4. Main conclusions The major divergences between lineages strongly support previously identified biogeographic barriers in eastern Australia based on studies of other taxa. These breaks appear to correlate with regions where the Great Escarpment is absent or obscure, suggesting topographic lowlands and the accompanying dry woodlands are a major barrier to dispersal for water skinks. While some river corridors, such as the Hunter Valley, were likely historically dry enough to inhibit the movement of Eulamprus populations, our data indicate that others, such as the Murray and Darling Rivers, are able to facilitate extensive gene flow through the vast arid and semi‐arid lowlands of New South Wales and South Australia. Comparing the patristic distances between the mitochondrial and AHE datasets highlights the continued value in analysing both types of data.

On the ecological significance of pollen color: a case study in American trout lily ( Erythronium americanum ) - Emily J. Austen; Shang‐Yao Lin; Jessica R. K. Forrest (Ecology, 2018)
Evolutionary ecologists seek to explain the processes that maintain variation within populations. In plants, petal color variation can affect pollinator visitation, environmental tolerance, and herbivore deterrence. Variation in sexual organs may similarly affect plant performance. Within‐population variation in pollen color, as occurs in the eastern North American spring ephemeral Erythronium americanum , provides an excellent opportunity to investigate the maintenance of variation in this trait. Although the red/yellow pollen‐color polymorphism of E. americanum is widely recognized, it has been poorly documented. Our goals were thus (1) to determine the geographic distribution of the color morphs and (2) to test the effects of pollen color on components of pollen performance. Data provided by citizen scientists indicated that populations range from monomorphic red, to polymorphic, to monomorphic yellow, but there was no detectable geographic pattern in morph distribution, suggesting morph occurrence cannot be explained by a broad‐scale ecological cline. In field experiments, we found no effect of pollen color on the probability of predation by the pollen‐feeding beetle Asclera ruficollis , on the ability of pollen to tolerate UV ‐B radiation, or on siring success (as measured by the fruit set of hand‐pollinated flowers). Pollinators, however, exhibited site‐specific pollen‐color preferences, suggesting they may act as agents of selection on this trait, and, depending on the constancy of their preferences, could contribute to the maintenance of variation. Collectively, our results eliminate some hypothesized ecological effects of pollen color in E. americanum , and identify effects of pollen color on pollinator attraction as a promising direction for future investigation.

Temporal Profile and Severity Correlation of a Panel of Rat Spinal Cord Injury Protein Biomarkers - Zhihui Yang; Helen M. Bramlett; Ahmed Moghieb; Dongnan Yu; Ping Wang; Fan Lin; Carl Bauer; Tyler M. Selig; Emily Jaalouk; Amanda S. Weissman; Disa S. Rathore; Pammela Romo; et al. (Molecular Neurobiology, 2018)

Conformational changes during human P2X7 receptor activation examined by structural modelling and cysteine-based cross-linking studies - Emily A Caseley; Stephen P Muench; Lin-Hua Jiang (Purinergic Signalling, 2017)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Quantitative identification of teratoma tissues formed by human embryonic stem cells with TeratomEye - Steve Kah Weng Oh; Pauline Chua; Koh Lin Foon; Emily Ng; Angela Chin; Andre Boon Hwa Choo; Rajagopalan Srinivasan (Biotechnology Letters, 2009)

Genetic diversities of the giant panda (Ailuropoda melanoleuca) in Wanglang and Baoxing Nature Reserves - Wei He; Ling Lin; Fujun Shen; Wenping Zhang; Zhihe Zhang; Emily King; Bisong Yue (Conservation Genetics, 2008)

Selective Contrast Enhancement of Individual Alzheimer’s Disease Amyloid Plaques Using a Polyamine and Gd-DOTA Conjugated Antibody Fragment Against Fibrillar Aβ42 for Magnetic Resonance Molecular Imaging - Muthu Ramakrishnan; Thomas M. Wengenack; Karunya K. Kandimalla; Geoffry L. Curran; Emily J. Gilles; Marina Ramirez-Alvarado; Joseph Lin; Michael Garwood; Clifford R. Jack Jr.; Joseph F. Poduslo (Pharmaceutical Research, 2008)

Picoplankton and nanoplankton and their trophic coupling in surface waters of the Sargasso Sea south of Bermuda - David A. Caron; Emily R. Peele; Ee Lin Lim; Mark R. Dennett (Limnology and Oceanography, 1999)
Studies were conducted during August and March–April in the Sargasso Sea south of Bermuda to examine rates of bacterial growth and picoplankton consumption by microbial consumers. Bacterial growth rates were estimated from [ 3 H]thymidine (TdR) incorporation rates, while grazing rates were determined using fluorescently labeled prey (FLP). In addition, net bacterial growth rates were calculated from changes in bacterial abundance during 24‐h incubations. The latter measurements were compared to net growth rates obtained by subtracting picoplankton grazing mortality rates from bacterial TdR growth rate estimates (TdR minus FLP). Overall, bacterial growth rates determined by TdR uptake were similar to FLP grazing rates during the March–April cruise, indicating an approximate balance between production and removal processes. Bacterial growth rates during August, however, were approximately twice the rates of grazer removal. Net bacterial growth rates determined from TdR growth rates minus FLP grazing rates were similar to net growth rates estimated from changes in abundance for samples collected near the surface during both cruises. However, rates of change of bacterial abundances during incubations were generally greater than rates predicted from TdR minus FLP for samples collected in the deep euphotic zone during both cruises. These discrepancies might be explained by several factors, including the inclusion of prochlorophytes in the bacterial counts and/or the stimulation of bacterial growth during containment. The TdR conversion factor also was an important consideration when comparing net bacterial growth rates estimated from changes in bacterial abundance to net growth rates determined from TdR minus FLP. Small nanoplanktonic protists (